Political Interests and Political Values: Methodological Aspects - Blagoeva, Blaga (Research Papers, 2021)
The article discusses some methodological issues in the study of interests and values ??in the philosophical and political science literature. An overview of the understanding of the nature and peculiarities of interests and values ??is made. An answer is sought to the question of their current understanding. Special emphasis is placed on the problem of the specifics of political interests and values ??and their role in the political process.
Keywords: Interest; Political interests; Political values; Value